Empirical analysis of credit relationships in small firms financing: Sampling design and descriptive statistics - Ralf Elsas; Sabine Henke; Achim Machauer; Roland Rott; Gerald Schenk (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
Despite the relevance of credit financing for the profit and risk situation of commercial banks only little empirical evidence on the initial credit decision and monitoring process exists due to the lack of appropriate data on bank debt financing. The present paper provides a systematic overview of a data set generated during the Center for Financial Studies research project on Credit Management which was designed to fill this empirical void. The data set contains a broad list of variables taken from the credit files of five major German banks. It is a random sample drawn from all customers which have engaged in some form of borrowing from the banks in question between January 1992 and January 1997 and which meet a number of selection criteria. The sampling design and data collection procedure are discussed in detail. Additionally, the project's research agenda is described and some general descriptive statistics of the firms in our sample are provided.
urn:nbn:de:hebis:30-9524
Keywords: G21; 330; credit management; credit-file data set